ASSESSMENT OF WORK POSTURE WITH THE APPLICATION OF THE REBA (Rapid Entire Body Assessment) METHOD - M. Mishbachul Khoiri; Moh. Jufriyanto; Akhmad Wasiur Rizqi (Sean Institute, 2023)
The REBA (Rapid Entire Body Assessment) method is developed in ergonomics. It can be used quickly to assess the working position or posture of an operator's neck, back, arms, wrists and legs. In accordance with the theory, namely REBA (Rapid Entire Body Assessment) is intended to analyze body shape and proper work position, using the REBA Map method you will see muscle complaints so that the company can control and maintain all operators, both in warehouses and production, so that The company can maintain the safety and health of its workers. Based on the results of observations made, it can be concluded that according to REBA calculations it was found that workers generally have a high level of risk, the highest value is 10, but there is 1 worker who has a low risk level with a value of 1.